2005
DOI: 10.1203/01.pdr.0000169402.13435.09
|View full text |Cite
|
Sign up to set email alerts
|

Effect of carbon dioxide on background cerebral electrical activity and fractional oxygen extraction in very low birth weight infants just after birth

Abstract: Decreased arterial carbon dioxide tension (PaCO 2 ) results in decreased cerebral blood flow, which is associated with diminished cerebral electrical activity. In such a situation, cerebral fractional oxygen extraction (CFOE) would be expected to increase to preserve cerebral oxygen delivery. This study aimed to determine whether changes in blood gases in infants less than 30 wk' gestation were associated with changes in background electroencephalograms (EEG) and CFOE. Thirty-two very low birth weight infants … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
52
0
3

Year Published

2006
2006
2019
2019

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 63 publications
(60 citation statements)
references
References 45 publications
5
52
0
3
Order By: Relevance
“…Abnormal background EEG activity characterized by prolonged interburst intervals has been linked to adverse neurologic outcome (22,23). The negative correlation between PaCO 2 and the relative power of the delta band suggested slowing of the EEG with hypocarbia (24). Suppression or prolonged discontinuity of the EEG occurred at MBP levels below 23 mm Hg (25).…”
Section: Discussionmentioning
confidence: 99%
“…Abnormal background EEG activity characterized by prolonged interburst intervals has been linked to adverse neurologic outcome (22,23). The negative correlation between PaCO 2 and the relative power of the delta band suggested slowing of the EEG with hypocarbia (24). Suppression or prolonged discontinuity of the EEG occurred at MBP levels below 23 mm Hg (25).…”
Section: Discussionmentioning
confidence: 99%
“…If, in fact, the hypercapnic-induced increase in cerebral blood flow was greater than that we recorded with laser-Doppler, CMRO 2 would not decrease as much, or perhaps even remain constant. One study also demonstrated that in very low birth weight newborns (birth weight Ͻ1500 g, gestation Ͻ30 wk), elevated PaCO 2 levels were associated with suppression of electroencephalographic activity (25). Nonetheless, this issue is controversial.…”
mentioning
confidence: 99%
“…The effects of pH, PcO 2 , and blood glucose concentration on EEG when babies are more than 48 h old differ from those noted in previous studies conducted during the first 48 h after birth. Victor et al (9) showed that lower levels of PcO 2 were associated with increased cerebral fractional oxygen extraction and slowing of EEG, while higher levels of PcO 2 were associated with suppression of EEG during the first 48 h of age. Granot et al (13) using amplitude integrated EEG on 65 preterm babies born before 28 wk gestational age showed that respiratory acidosis and hyperglycemia during the first 72 h after birth was associated with suppressed electrical activity.…”
Section: Permissive Hypercapnia and Eegmentioning
confidence: 99%
“…Prolonged EEG IBIs of more than 30 s in preterm infants born at less than 28 wk gestation and more than 25 s in preterm infants born at more 28 wk gestation have been associated with increased incidence of death or developmental motor abnormalities (6,7). EEG has been studied in relation to age, hypotension, hypo and hypercapnia, and cardiac output in preterm babies born before 30 wk gestation during the first 72 h after birth (8)(9)(10)(11). Lower levels of blood carbon dioxide have been associated with slowing of cerebral electrical activity and increased cerebral fractional oxygen extraction, while hypercapnia was associated with suppression of cerebral electrical activity during the first 48 h after birth (9).…”
mentioning
confidence: 99%
See 1 more Smart Citation